The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3233/jad-2012-121231
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-Rich Mineral Water as a Non-Invasive Test of the ‘Aluminum Hypothesis’ in Alzheimer's Disease

Abstract: There has been a plausible link between human exposure to aluminum and Alzheimer's disease for several decades. We contend that the only direct and ethically acceptable experimental test of the 'aluminum hypothesis', which would provide unequivocal data specific to the link, is to test the null hypothesis that a reduction in the body burden of aluminum to its lowest practical limit would have no influence upon the incidence, progression, or severity of Alzheimer's disease. Herein we are testing the hypothesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 20 publications
(26 reference statements)
3
40
0
Order By: Relevance
“…On the contrary, aluminum reduction was actually correlated directly to the consumption of M-OSA and MMST. This effect is in accordance with the literature: epidemiological studies already suggested that silicon can prevent the absorption of aluminum and/or increase its excretion [31][32][33][34]. Indeed, in nature, silicon readily forms complexes with aluminum and therefore, aluminosilicates are the most prevalent form of silicates [3].…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary, aluminum reduction was actually correlated directly to the consumption of M-OSA and MMST. This effect is in accordance with the literature: epidemiological studies already suggested that silicon can prevent the absorption of aluminum and/or increase its excretion [31][32][33][34]. Indeed, in nature, silicon readily forms complexes with aluminum and therefore, aluminosilicates are the most prevalent form of silicates [3].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, they documented that regular drinking of a silicon-rich mineral water during a period of 3 months significantly reduced the body burden of aluminium. Similar results were obtained by Davenward et al [79] who showed that silicon-rich mineral waters can be used as a non-invasive method to reduce the body burden of aluminium in both Alzheimer's patients and control group by facilitating the removal of aluminium via the urine without any concomitant effect. They also showed clinically relevant improvements of cognitive performances in at least 3 out of 15 individuals with Alzheimer disease.…”
Section: Therapeutic and Biological Effects Of Ortho-silicic Acid Andsupporting
confidence: 86%
“…We have also been investigating non-invasive ways to reduce the uptake of aluminium into the body and, importantly, to facilitate the excretion of aluminium from the body. We were successful in lowering the body burden of aluminium in individuals with moderateto-severe AD and concomitantly we were able to demonstrate clinically significant improvements in cognitive performance in some individuals [14]. These experiments offer some hope that the aluminium hypothesis of AD, and indeed other neurodegenerative diseases, might be tested by lowering the body burden of aluminium in affected individuals.…”
Section: Aluminium An Everyday Neurotoxinmentioning
confidence: 75%